Implemention of Washing Machine to Increase The Production Capacity of Sweet Potato : Implementasi Mesin Pencuci untuk Meningkatkan Kapasitas Produksi Ubi Jalar - Gusri Akhyar Ibrahim; Indra Hermawan; Arinal Hamni; Dewi Sartika; Subeki; Ahmad Su’udi (Program Studi Teknik Mesin, Fakultas Teknik Universitas Bengkulu, 2025)
The rotary system sweet potato washing machine is used to clean sweet potatoes that are dirty and contain lots of soil and other impurities such as microorganisms. The rotary system which rotates and rolls is used for perfect movement, so that the dirt covering the sweet potato is removed completely. The aim of this activity is to test and determine the production capacity of the rotary system of sweet potato washing machines used by sweet potato collecting farmers. The testing was carried out by putting a number of sweet potatoes into the washing tub, along with running water as a cleaning fluid. The drum is rotated with a rotation speed of 1430 rpm which is connected to a gear ratio of 1:30, so the rotation speed is smaller. The stirring arm is moved simultaneously with the movement of the drum. The rotating stirrer arm will provide a more dynamic movement so that the adhering soil will be removed from the surface of the sweet potato, as the washing water flows. The test results showed that the process of washing the sweet potatoes was successful, where the sweet potatoes that had dirt attached to them came off completely. The production capacity of the sweet potato washing machine is 50 kg, with a washing time of 5 minutes. The production cycle for a rotary system sweet potato washing machine is 15 minutes while manual washing is 40 minutes. Meanwhile, the productivity of rotary system washing sweet potatoes can reach 180 kg/hour. The production costs required for the equipment are IDR. 539,-/hour.